Fouling Analysis on Polysulfone/Peg400/ZnO Membrane during Textile Wastewater Treatment - Putu Teta Prihartini Aryanti; Febrianto Adi Nugroho; Gatra Buana Winiarti; Ghina Shofi Pratiwi; I Nyoman Widiasa (Reaktor)
Fouling has become the main problem in long-term application of ultrafiltration (UF) membrane for water and wastewater treatment, significantly reducing membrane productivity. In this paper, fouling on polysulfone-based membrane was analyzed using Hermia’s model during textile wastewater treatment. The UF membrane has been prepared by blending polysulfone (PSf), acetone, and PEG400 in DMAc, with ZnO nanoparticles at a concentration of 1% by weight of polymers (PSf and PEG400). The influence of polysulfone concentration (18 and 20 wt.%) and PEG400 (0 - 25 wt.%) on fouling mechanisms was investigated. It was found that the increase of polysulfone from 18 to 20 wt.% reduced permeate flux from 54 to 25 L.m-2.h-1. Vise versa, the increase of PEG400 concentration enhanced the permeate flux. More stable flux was achieved when 18 wt.% of polysulfone was used to prepare the UF membrane. The fouling type in the UF membrane depends on the characteristics of the membrane. A significant flux decline occurred when used 20 wt.% of polysulfone without the addition of PEG400. Smaller membrane pore and higher hydrophobicity due to high polysulfone concentration induced cake layer of fouling on the membrane surface at the first 40 minutes of ultrafiltration. Further increase of operating time, internal fouling was formed due to the movement of pollutants to the permeate side caused by different concentrations. The highest color rejection (86%) was achieved when 25 wt.% of PEG400 was added in 20 wt.% of polysulfone solution.